Avaliação de qualidade de amidos de mandioca modificados utilizados na fabricação de pão de queijo - Calandrin, Gisele Borin [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The food industry looks for new ways and strategies to standardize the marketing products in the customer market. The modification of the cornflour that are produced in the manufacturing of the cheese bread has been one of the these ways, since some raw materials that are used to make the cornflour present different features in each supplyed allotment. The present research had as a main purpose to analyse such features looking forward to improving the quality of the final product. Thus, some tests were done to verify the pH, humidity and acidity; it was checked the percentage of carbonyl and carboxylic groups and the power of expansion to five different allotments and to farina, for example: pre-gel, natural, expandex farina as the combination of the three cited kinds. After diversifying the allotments, different results were acquired, even to an unique kind of farina and it was not possible to correlate the results of acidity, the percentage of carbonyl and carboxylic groups and the power of expansion. The pH and humidity are proper for each kind of farina. This way, the raw materials that are used for each cheese bread manufacturing must be analysed in each allotment

A indústria alimentícia busca novas formas e estratégias para padronizar os produtos comercializados no mercado consumidor. A modificação dos amidos utilizados na fabricação de pão de queijo tem sido uma dessas estratégias, já que matérias-primas utilizadas para produzi-lo apresentam características distintas a cada lote fornecido. O presente trabalho teve como objetivo analisar tais características a fim de melhorar a qualidade do produto final. Deste modo, foram realizados testes de pH, umidade, acidez titulável, teor de grupos carbonílicos e carboxílicos e poder de expansão para cinco lotes diferentes e para féculas do tipo: pré-gel, natural, expandex e combinação dos três tipos citados. Variando-se os lotes, obtiveram-se resultados diferentes, até mesmo para um único tipo de fécula e não foi possível correlacionar os resultados de acidez titulável, teor de grupos carbonílicos e carboxílicos com o poder de expansão. O pH e a umidade são peculiares para cada tipo de fécula. Sendo assim, as matérias-primas utilizadas para cada produção de pão de queijo devem ser analisadas a cada lote
Keywords: Pão; Fecula; Amido; Alimentos - Analise; Alimentos - Industria; Bread; Starch; Food - Analysis; Food industry and trade